2012
DOI: 10.1002/ijc.27425
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukemia around French nuclear power plants—The geocap study, 2002–2007

Abstract: The aim of this work is to study the risk of childhood acute leukemia (AL) around French nuclear power plants (NPPs). The nationwide Geocap case-control study included the 2,753 cases diagnosed in mainland France over 2002-2007 and 30,000 contemporaneous population controls. The last addresses were geocoded and located around the 19 NPPs. The study used distance to NPPs and a dose-based geographic zoning (DBGZ), based on the estimated dose to bone marrow related to NPP gaseous discharges. An odds ratio (OR) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 39 publications
5
73
1
1
Order By: Relevance
“…After Sellafield, increased childhood leukemia risk was found at nearly all the nuclear sites where studies were carried out [7][8][9][10] and a very large study from Germany also confirmed a statistically significant excess risk [8]. The latest COMARE 17 th report continues to dismiss the possibility that the radiation exposures can be the cause of the leukemias, and for the same reason, the doses are too low [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After Sellafield, increased childhood leukemia risk was found at nearly all the nuclear sites where studies were carried out [7][8][9][10] and a very large study from Germany also confirmed a statistically significant excess risk [8]. The latest COMARE 17 th report continues to dismiss the possibility that the radiation exposures can be the cause of the leukemias, and for the same reason, the doses are too low [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since childhood leukemia has been associated in many studies [4][5][6][7][8][9][10] with proximity to nuclear sites, in particular fuel reprocessing sites like Sellafield in the UK [10] it seems possible that radioactive exposures of some kind may be reasonably investigated as a cause. The largest injection of radioactivity into the global environment was the atmospheric nuclear testing that was carried out in the period 1950-1963 when the fallout contamination peaked in 1959-63.…”
Section: Introductionmentioning
confidence: 99%
“…4 and the discussion of the Geocap study. 2 Adjusting for community type did not alter the odds ratio for ''distance'' in Germany ( Table 1).…”
Section: Dear Sirmentioning
confidence: 93%
“…2 The Geocap study used a similar design as the KiKK study: in a case-control study, the distance to the next nuclear power plant was used as a surrogate for potential exposure to ionizing radiation from the plant. The Geocap study had two major extensions compared to the German study: cases and controls up to age 15 were included in the study (in Germany, the age limit was 5 years) and a further classification of exposure according to a so-called ''Dose-Based Geographical Zoning'' was performed.…”
Section: Dear Sirmentioning
confidence: 99%
“…1 They particularly commented on the standardized incidence ratio (SIR) we showed in Table 2 for children less than 5-years-old over the whole study period [1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007] Table 2). …”
Section: Dear Editormentioning
confidence: 99%